2020
DOI: 10.17352/2455-5479.000091
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on quality of life and well-being in Morocco

Abstract: Introduction: The majority of epidemiological reports focus on confi rmed cases of COVID-19. In this study, we aim to assess the health and well-being of adults not infected with Covid-19 after two months of quarantine in Morocco. Materials and methods: Two months after the declaration of quarantine in Morocco following the Covid-19 epidemic, we carried out a descriptive cross-sectional study of 279 Moroccan citizens. We used the Short Form Health Survey (SF-12) as a determinant of quality of life, which is ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
31
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 19 publications
10
31
1
1
Order By: Relevance
“…Findings from different studies have reported the psychosocial impact of the pandemic at the level of individual well-being of the person, in form of psychological symptoms such as emotional disorders, depression, stress, irritability, insomnia, post-traumatic stress, anger or emotional exhaustion [12,20]; risk behaviors such as increased substance abuse [21]; or decreased perceived health [22]. However, these responses also affect the level of community well-being [23][24][25]. The WHO recommends paying special attention to social participation, which plays an important role in the different dimensions of well-being [26], especially in the life satisfaction [27,28], defined as the estimation of quality of life based on the preferences and complacency of an individual with respect to the different dimensions of their life [29].…”
Section: Introductionmentioning
confidence: 99%
“…Findings from different studies have reported the psychosocial impact of the pandemic at the level of individual well-being of the person, in form of psychological symptoms such as emotional disorders, depression, stress, irritability, insomnia, post-traumatic stress, anger or emotional exhaustion [12,20]; risk behaviors such as increased substance abuse [21]; or decreased perceived health [22]. However, these responses also affect the level of community well-being [23][24][25]. The WHO recommends paying special attention to social participation, which plays an important role in the different dimensions of well-being [26], especially in the life satisfaction [27,28], defined as the estimation of quality of life based on the preferences and complacency of an individual with respect to the different dimensions of their life [29].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have examined QOL using general instruments, such as the SF-36 (24,25) and the SF-12 (26). Some other studies have used instruments measuring psychological problems and social support that do not seem to properly assess QOL (2,27). Therefore, it seems necessary to have a scale specifically assessing QOL.…”
Section: Introductionmentioning
confidence: 99%
“…The ongoing COVID-19 pandemic has already disrupted people’s quality of life. 1–4 The outbreak originated from Wuhan, China, one year ago; still, it is not controlled. As all of the countries were attacked by the virus, people were at higher risk of being infected except those following preventive measures.…”
Section: Introductionmentioning
confidence: 99%